2019
DOI: 10.3390/geosciences9080329
|View full text |Cite
|
Sign up to set email alerts
|

A Quick-Look Method for Initial Evaluation of Gas Hydrate Stability below Subaqueous Permafrost

Abstract: Many studies demonstrated the coexistence of subaqueous permafrost and gas hydrate. Subaqueous permafrost could be a factor affecting the formation/dissociation of gas hydrate. Here, we propose a simple empirical approach that allows estimating the steady-state conditions for gas hydrate stability in the presence of subaqueous permafrost. This approach was derived for pressure, temperature, and salinity conditions typical of subaqueous permafrost in marine (brine) and lacustrine (freshwater) environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Generally, hydrates accumulate anywhere in the ocean-bottom sediments where water depth exceeds about 400 m (Figure 1). In Polar Regions, in presence of sub-seawater permafrost, the hydrate could be stable at shallower water as demonstrated recently by [2,3]. Very deep (abyssal) sediments are generally not thought to house hydrates in large quantities due to the lack of high biologic productivity (necessary to produce the organic matter that is converted to methane) and rapid sedimentation rates (necessary to bury the organic matter), both necessary for hydrate formation on the continental shelves.…”
Section: Introductionmentioning
confidence: 94%
“…Generally, hydrates accumulate anywhere in the ocean-bottom sediments where water depth exceeds about 400 m (Figure 1). In Polar Regions, in presence of sub-seawater permafrost, the hydrate could be stable at shallower water as demonstrated recently by [2,3]. Very deep (abyssal) sediments are generally not thought to house hydrates in large quantities due to the lack of high biologic productivity (necessary to produce the organic matter that is converted to methane) and rapid sedimentation rates (necessary to bury the organic matter), both necessary for hydrate formation on the continental shelves.…”
Section: Introductionmentioning
confidence: 94%
“…The state of the GHSZ within the permafrost area strongly depends on the ground temperature and pressure, that is why the calculations were conducted with the phase curves of methane hydrate under the corresponding lithostatic pressure. In accordance with [43], the pressure in the ground layer was calculated as the hydrostatic column pressure beneath the frozen layer at the study depth and as the lithostatic pressure at the bottom of permafrost. Figure 3.…”
Section: Description Of the Numerical Modelmentioning
confidence: 99%
“…The calculations of the thermal state of bottom sediments are accompan thermal dynamic boundaries of the methane gas hydrates stability zone (Fig the GHSZ within the permafrost area strongly depends on the ground tem that is why the calculations were conducted with the phase curves of meth corresponding lithostatic pressure. In accordance with [43], the pressure in calculated as the hydrostatic column pressure beneath the frozen layer at the lithostatic pressure at the bottom of permafrost.…”
Section: Description Of the Numerical Modelmentioning
confidence: 99%
“…Many studies have demonstrated the coexistence of subaqueous permafrost, gas hydrate and the effect of the subaqueous on their formation/dissociation, i.e., [37]. Nevertheless, before Reference [38], an empirical method, which allows for an easy initial estimation of the conditions sufficient to have the stability of hydrate below subaqueous permafrost in absence of direct geological or geophysical data, was missed. In this Special Issue, for the first time a quick-look method that allows estimating the steady-state conditions for gas hydrate stability in the presence of subaqueous permafrost is presented.…”
Section: Arcticmentioning
confidence: 99%